High-class apartment selection factors in Ho Chi Minh City - Nguyen Thanh Phong; Nguyen Anh Thu; Le Thi Thuy An (Ho Chi Minh City Open University Journal of Science - Engineering and Technology, 2022)
This paper aims to find out the current state of the high-class apartment market. Qualitative research is done to adjust and supplement the observed variables for the scale. Quantitative research is conducted through a survey of customers who have bought a high-class apartment or are intending to buy an apartment to build a research model and test the scale. After collecting data, the study conducted the descriptive statistical analysis, testing the reliability of scale. Then, the Exploratory Factor Analysis (EFA) was performed to group the related factors into groups of factors that are independent. The research results showed that there are eight main groups of factors with 31 related observational variables that affected customers' decisions to choose high-class apartments.